2011
DOI: 10.1007/s12640-011-9238-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Docosahexaenoic Acid on Visual Evoked Potentials in a Mouse Model of Parkinson’s Disease: The Role of Cyclooxygenase-2 and Nuclear Factor Kappa-B

Abstract: This study aimed to investigate the effect of docosahexaenoic acid (DHA) on visual evoked potentials (VEPs) in a mice model of Parkinson's disease (PD). Mice model was created by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and DHA was given by gavage. Cyclooxygenase-2 (COX-2), caspase-3 activities, nuclear factor kappa-B (NF-κB) and prostaglandin E2 (PGE2) levels were determined in substantia nigra (SN) and retina. Cyclooxygenase-2 intensities were also determined immunohistochemically. The tyrosine hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…VEPs represent relevant information on determining the integrity of the visual system and have an accepted clinical utility regarding visual and other neuropathologies (Chiappa and Ropper, 1982;Halliday et al, 1972;Ozsoy et al, 2011;Wright et al, 1986). In addition to this, it is well known that VEPs are a sensitive method for detecting early alterations of optic pathway in experimental toxicology studies (Agar et al, 2000;Aydin et al, 2005;Kucukatay et al, 2006a;Otto et al, 1988;Savcioglu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…VEPs represent relevant information on determining the integrity of the visual system and have an accepted clinical utility regarding visual and other neuropathologies (Chiappa and Ropper, 1982;Halliday et al, 1972;Ozsoy et al, 2011;Wright et al, 1986). In addition to this, it is well known that VEPs are a sensitive method for detecting early alterations of optic pathway in experimental toxicology studies (Agar et al, 2000;Aydin et al, 2005;Kucukatay et al, 2006a;Otto et al, 1988;Savcioglu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the prostaglandin PGE2, a derivative of AA via cyclooxygenase-2 (COX-2), can induce neurotoxic effects on subpopulations of SN dopaminergic neurons in a dose and receptor-dependent manner (Carrasco et al, 2007). Furthermore, it has been also shown that dietary treatment with DHA caused a significant decrease in COX-2 activity and PGE2 levels in mice SN, reducing MPTP-induced dopaminergic cell death (Ozsoy et al, 2011).…”
Section: Repercussion Of Dietary Treatment On the Number Of Dopaminermentioning
confidence: 99%
“…In the present study, the DHA dose was selected according to previous studies [28][29][30][31][32][33]. Daily intake of DHA was used with different doses in different experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were randomly divided into four experimental groups as follows: (1) control; (2) DHA-treated; (3) MPTP-induced; (4) MPTP-induced + DHA-treated. DHA (Sigma-Aldrich, St. Louis, MO, USA) was dissolved in corn oil at a concentration of 0.046 M and was given to the treatment groups for 30 days (36 mg/kg/day) by gavage [28][29][30][31][32][33]. In order to eliminate the effects of daily gavage and vehicle, the control and MPTP-induced rats received a similar volume of corn oil alone.…”
Section: Methodsmentioning
confidence: 99%